(untitled) (Revista de Administração, 2012)
Though expatriation has become common in today's corporate world and the majority of expatriates are self-initiated rather than assigned by business organizations to work abroad, many authors have treated these two groups of expatriates (self-initiated and organizational) as homogeneous. The objective of this study was to differentiate, conceptually and empirically, self-initiated and organizational expatriates, by examining differences in the adaptation of individuals from both groups in Brazil. The study was qualitative, conducted through semi-structured interviews with 21 organizational and 24 self-initiated expatriates living in Brazil, using content analysis. The theoretical perspective adopted in this study was the model of transcultural adaptation of expatriates of Black, Mendenhall and Oddou (1991). The results emphasize the importance of a conceptual and empirical separation of the two types of expatriates, as they showed different characteristics in the three dimensions of transcultural adaptation used in this study. For Human Resources professionals that work with expatriation processes, the authors suggest that self-initiated expatriates are an advantageous option for the creation of a global workforce, since they tend to adapt better than the organizational ones. For academics, the authors recommend that both types of expatriates be considered in future research, given their specificities